2013
DOI: 10.1136/gutjnl-2012-303018
|View full text |Cite
|
Sign up to set email alerts
|

Association betweenHelicobacter pyloriand mortality in the NHANES III study

Abstract: Objective Persistent colonization by Helicobacter pylori, and especially by cagA-positive strains, has been related to several health outcomes with effects in opposite directions. Thus, it is important to evaluate its influence on both total and category-specific mortality. Design We conducted prospective cohort analyses in a nationally representative sample of 9895 participants enrolled in the National Health and Nutrition Examination Survey III (NHANES III) to assess the association of H. pylori status wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 59 publications
2
82
2
5
Order By: Relevance
“…The positive association of H. pylori infection with CVD was first reported in a case-control study 4) in which individuals with H. pylori seropositivity had an increased risk, approximately two-fold, of developing CVD. However, not all subsequent studies have supported these results [5][6][7][8][9][10][11][12][13] . For example, a 1998 meta-analysis of 18 studies found no significant association between H. pylori and risk of coronary heart disease (CHD), a major component of CVD 14) .…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…The positive association of H. pylori infection with CVD was first reported in a case-control study 4) in which individuals with H. pylori seropositivity had an increased risk, approximately two-fold, of developing CVD. However, not all subsequent studies have supported these results [5][6][7][8][9][10][11][12][13] . For example, a 1998 meta-analysis of 18 studies found no significant association between H. pylori and risk of coronary heart disease (CHD), a major component of CVD 14) .…”
Section: Introductionmentioning
confidence: 70%
“…The majority of previous research on the above association was conducted in Western countries [5][6][7][8][9][10][11][12][13] and findings have been inconsistent and inconclusive. It is possible, however, that variations in the study tion to H. pylori seropositivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the initial observations and molecular biology studies, it would seem to indicate that H. pylori is a dreaded noxious pathogen. However, a number of studies, notably epidemiological ones, have also indicated inverse correlations, odds ratios significantly less than one, for a number of serious health problems, in persons harboring cagA+ strains [39]. Further studies in selected populations may help to shed light on these Table 2.…”
Section: H Pylori Colonization Vs Infectionmentioning
confidence: 99%
“…This suggests that H. pylori cagA+ is an important director, perhaps playing a keystone species role in the stomach of many persons. Given the rising appreciation of the importance of the microbiota in determining health and disease, H. pylori may thus represent a key to understanding the multidimensional activities that go on at the humanbacterial interface [33][34][35][36][37][38][39][40][41][42]. For this reason, H. pylori presents a number of important opportunities toward gaining better insight into both bacterial and host biology and interactions.…”
Section: H Pylori Colonization Vs Infectionmentioning
confidence: 99%